Competition in Regional Housing Markets and Its Government Regulation - Pavlov, Kostiantyn V.; Павлов, Костянтин Володимирович (My University, 2018)
In this article the author outlines the government role in the process of regulating competitive relations in the regional residential real estate markets in Ukraine. The current tendencies and situation dominating the housing market in the country and its regions are explicated. Since the housing market in this country is incapable to independently handle the general processes of self-regulation, the author proves the need for government intervention in its regional processes. An effectively targeted infrastructure greatly enhances the competitiveness of local markets and provides a process for continuous reproduction of their competitive advantages. The main problems arising in the government antimonopoly insurances of market processes are singled out. The in-depth study of existing and prospective ways of market value assessment analysis has been suggested. The priority directions of government provision of the antitrust implementation policy have been clarified. The devices are offered to sustain control over the indicators of regional housing markets.

В данной статье автором обозначены роль государства в процессе регулирования конкурентных отношений на региональных рынках жилой недвижимости Украины. Показаны современные тенденции и положение, царящие на рынке жилья в стране и ее регионах. Поскольку рынок жилья в стране не способен самостоятельно справиться с процессами саморегулирования, автором доказана необходимость в государственном вмешательстве в его происходящие на региональном уровне процессы. Ведь эффективно направлена инфраструктура в значительной степени повышает уровень конкурентоспособности локальных рынков и обеспечивает процесс постоянного воспроизводства их конкурентных преимуществ. Выделены основные проблемы, возникающие в процессе реализации государственного антимонопольного обеспечения рыночных процессов. Углубленно исследованы существующие и предложены новые пути анализа и оценки рыночной веса. Определены четкие, приоритетные направления обеспечения реализации антимонопольной политики со стороны государства. Предложены инструменты, способствующие обеспечению контроля за показателями региональных рынков жилья.
Конкуренция на региональных рынках жилья и обеспечение ее регулирования со стороны государства
Keywords: government regulation; antimonopoly policy of the state; competition; competition regulation; competition in the region; competition in regional residential real estate markets; housing market; housing relations; regional dimension of housing market; local market